PdeERF114 recruits PdeWRKY75 to regulate callus formation in poplar by modulating the accumulation of H2 O2 and the relaxation of cell walls - Zhang, Yan (The New phytologist, 2024)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.